Apocynaceae Juss. s.l. from the restingas of Pará, Brazil - Pereira, Ivete da Silva; Santos, João Ubiratan Moreira dos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
This is a floristic study of Apocynaceae s.l. from sandbanks of Pará. Descriptions, illustrations and dichotomous keys of the species, as well as information on geographical distribution, phenology and taxonomic comments are given. The Apocynaceae s.l. from sandbanks in the State of Pará is represented by 12 species in 11 genera. The more representative genus was Mandevilla Lindl., with two species. Calotropis procera (Aiton) W.T. Aiton and Allamanda cathartica L. are subspontaneous species, of which the first one is an exotic species and the latter one a new record for the sandbanks of the State of Pará. The largest number of species was collected in the formation Dunefield.